The Transformation of Religious Practices of Digital Ummah in the Age of Algorithms - Imam Alfi; Abdul Basit; Umi Halwati; Abdul Malik (Balai Penelitian dan Pengembangan Agama Makassar, 2026)
Non-Indexed Publication